2018
DOI: 10.1371/journal.pone.0207096
|View full text |Cite
|
Sign up to set email alerts
|

Patient clusters based on HbA1c trajectories: A step toward individualized medicine in type 2 diabetes

Abstract: AimsTo identify clinically meaningful clusters of patients with similar glycated hemoglobin (HbA1c) trajectories among patients with type 2 diabetes.MethodsA retrospective cohort study using unsupervised machine learning clustering methodologies to determine clusters of patients with similar longitudinal HbA1c trajectories. Stability of these clusters was assessed and supervised random forest analysis verified the clusters’ reproducibility. Clinical relevance of the clusters was assessed through multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…Only two studies have indicated reducing the dimensionality of the data prior to CA [12,13]. The widespread method for clustering among included publications was k-means clustering [7,8,13,[15][16][17][18]20]. Several studies performed k-means analysis only for GADA-negative individuals [7,8,18].…”
Section: Methods Of Clustering and Dimensionality Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies have indicated reducing the dimensionality of the data prior to CA [12,13]. The widespread method for clustering among included publications was k-means clustering [7,8,13,[15][16][17][18]20]. Several studies performed k-means analysis only for GADA-negative individuals [7,8,18].…”
Section: Methods Of Clustering and Dimensionality Reductionmentioning
confidence: 99%
“…In addition, two publications determined the number of clusters based on principal component analysis (PCA) [12,13], one publication performed a "NbClust" algorithm that selected an optimal method for the determination of number of clusters [15], one study was based within the cluster sums of squares against the number of clusters [16], one study was based on a cosine distance metric [19].…”
Section: Variables Selected For Cluster Analysismentioning
confidence: 99%
“…Beyond the intense discussion on what exactly ML means and its pros and cons compared to “classical” statistical modelling methods, it is worth noting that the use of ML algorithms in medicine has received a wider attention following the demonstration of a performance similar to human clinical decision in the field of diabetes medicine, namely the diagnosis of diabetic retinopathy . ML models have been applied in diabetes to define clusters of diabetes phenotypes; predict kidney disease, hypoglycaemia, or glucose control; identify risk factors for CVD and death in diabetes; develop prediction models for complications; or transport RCT data to a target population …”
Section: Future Applications Of Rwe In Diabetes Researchmentioning
confidence: 99%
“…Prediction models based on such traditional regression analyses, however, have limited utility for clinical decision‐making because they do not personalize the prediction to the individual. Similarly, studies that identify clinical characteristics of patients that are associated with distinct HbA1c trajectories in patients with T2DM over the course of insulin treatment via unsupervised clustering algorithms cannot sufficiently guide clinical decision‐making . Such studies lead to inconsistent groupings of patients, suggesting that cluster analysis driven by outcome patterns is not helpful in predicting HbA1c responses using clinical variables at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies that identify clinical characteristics of patients that are associated with distinct HbA1c trajectories in patients with T2DM over the course of insulin treatment via unsupervised clustering algorithms cannot sufficiently guide clinical decision-making. [14][15][16][17][18] Such studies lead to inconsistent groupings of patients, suggesting that cluster analysis driven by outcome patterns is not helpful in predicting HbA1c responses using clinical variables at baseline. There is a need for a more individualized approach to support clinical decision-making and to guide personalized treatment for patients with T2DM in need of additional treatment.…”
Section: Introductionmentioning
confidence: 99%